2003
DOI: 10.1021/jp0340616
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Solution Anion on the Mechanism of Transpassive Dissolution of Ferrous- and Nickel-Based Alloys

Abstract: The aim of this work is to generalize the model for the transpassive dissolution of ferrous-and nickel-based alloys in acidic solutions by assessing the effect of the solution anion on the individual steps of the process. First, experimental voltammetric and impedance spectroscopic data on transpassive dissolution of pure Cr, Fe-12%Cr, Fe-12%Cr-5%Mo, Fe-25%Cr, Fe-25%Cr-10%Mo, pure Ni, Ni-10%Cr, and Ni-20%Cr in phosphoric acid solution are compared with earlier data for the same materials in sulfuric acid solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…The interface becomes active due to the charge transfer and the two different adsorption processes occurring at the interface. The appearance of an inductive loop at low frequencies at the transpassive potential range of some metals in acidic solutions has been reported previously [9][10][11][12][13][14][15][16].…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The interface becomes active due to the charge transfer and the two different adsorption processes occurring at the interface. The appearance of an inductive loop at low frequencies at the transpassive potential range of some metals in acidic solutions has been reported previously [9][10][11][12][13][14][15][16].…”
Section: Resultssupporting
confidence: 68%
“…At potentials of 1.15 and 1.25 V versus SCE, it is clear that two positive inductive loops are formed. The capacitive loop appearing at high to medium frequencies is attributable to the parallel combination of the charge-transfer resistance and interfacial capacitance; the inductive loop at low frequencies reflects the relaxation of the surface coverage of an intermediate adsorption reaction [11][12][13][14][15][16]. In this study, we found that two lowfrequency inductive loops exist, indicating the adsorption of two intermediates.…”
Section: Discussionmentioning
confidence: 51%
“…The experiments were carried out at 20±1 °C in naturally aerated solutions. The compositions of the electrolyte selected on the basis of its electropolishing and surface levelling ability was 13.5M H 3 PO 4 -0.5 M H 2 SO 4 -2 M C 3 H 5 (OH) 3 .The high-temperature measurements have been performed in molten p.a. KH 2 PO 4 at a temperature of 270 ± 5 °С.…”
Section: Methodsmentioning
confidence: 99%
“…The Cr-transpassive potential was increased by decreasing the pH. In buffer solutions, secondary passivation [10,13] occurred at potentials noble to 0.6 V SCE (pH 8.5) or 0.9 V SCE (pH 4.0), presumably due to the enrichment of Fe and Ni that exhibit passivity at this high potential region [11,12]. However, the secondary passivation feature almost disappeared in sulfate solutions, especially at a pH of 2.0.…”
Section: Methodsmentioning
confidence: 97%
“…A borate solution is beneficial for the passivation of alloys, while chloride is detrimental for the formation of stable passive film [9]. Bojinov et al [10] reported that Fe-Cr and Ni-Cr alloys show a stable secondary passivation feature in a 1 M H 3 PO 4 solution but not in a 1 M H 2 SO 4 solution. He also found that the transpassive dissolution rate of Ni is significantly lower in phosphoric acid solutions than in sulfuric acid solutions, whereas that of Cr is faster in phosphoric acid solutions than in the other.…”
Section: Introductionmentioning
confidence: 99%